2018
DOI: 10.23958/ijsei/vol04-i08/02
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Market Orientation and Product Innovation on the Competitive Advantage and Its Implication toward Small and Medium Enterprises (Ukm) Performance

Abstract: This study aims to: (1) determine the effect of market orientation on competitive advantage; (2) to know the effect of innovation on competitive advantage; (3) to know the influence of market orientation and product innovation together to competitive advantage; (4) the effect of market orientation on the performance of SMEs, (5) to know the effect of product innovation on the performance of SMEs, (6) to know the effect of competitive advantage on SMEs performance, and (7) to know the effect of market orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
1
26

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 0 publications
7
38
1
26
Order By: Relevance
“…The result of hypothesis testing indicates that product innovation has a positive effect on competitive advantage. The results of this study are in line with the results of Herman et. al.…”
Section: Marketsupporting
confidence: 93%
“…The result of hypothesis testing indicates that product innovation has a positive effect on competitive advantage. The results of this study are in line with the results of Herman et. al.…”
Section: Marketsupporting
confidence: 93%
“…Penelitian "yang dilakukan oleh Herman et al (2018) menunjukkan bahwa orientasi pasar memiliki pengaruh yang positif terhadap keunggulan bersaing. Orientasi pasar memiliki tiga komponen: orientasi pelanggan, orientasi pesaing dan koordinasi antar fungsi.…”
Section: Pendahuluanunclassified
“…Perusahaan yang menerapkan orientasi pasar memiliki kelebihan dalam hal pengetahuan pelanggan dan kelebihan ini dapat dijadikan sebagai sumber untuk menciptakan produk yang sesuai dengan keinginan dan kebutuhan pelanggan. Penelitian yang dilakukan oleh Herman et al (2018) menunjukkan bahwa orientasi pasar memiliki pengaruh yang positif terhadap keunggulan bersaing. "…”
Section: Tabel 5 Deskripsi Jawaban Responden Terhadap Strategi Diferunclassified
“…Product innovation is one determinant of business performance (Mahmud & Hasyim, 2018;Herman et al, 2018). The speed of product innovation will affect the success of the product in the market and have an impact on improving the company performance, such as the growth of market share, sales, and profits (Mitrega et al, 2017).…”
Section: Product Innovation Agility and Business Performancementioning
confidence: 99%
“…Some previous studies showed inconsistent results. Market orientation can improve business performance Takata, 2016;Zainul & Utami, 2016;Kaswuri, 2016;Masa'deh et al, 2018;Herman & Arafah, 2018;Bhattarai & Tasavori, 2019). Other studies showed that market orientation is not able to improve business performance (Keskin, 2006;Mahmoud et al, 2016;Solano & Collado, 2018;Idrus & Abdussakir, 2018).…”
Section: Introductionmentioning
confidence: 98%